SELEKSI CALON PESERTA OLIMPIADE SAINS MENGGUNAKAN FUZZY MULTIPLE ATTRIBUTE DESICION MAKING (FMADM) (Study Kasus : Fatih Bilingual School) - Rizal Rizal (TECHSI - Jurnal Teknik Informatika, 2014)
At Fatih Bilingual School the team of olympiad sains (OSN) it depend on whether marks of subject wheareas the olympiad test in the city, province, and national needed something inteligency and experience about olympiad. The type of samples are 4 subject about sains, there are chemistry, physic, mathematics, and biology. The purpose of this research were to help and chooise the olympiad student by Fuzzy Weighted Product (WP) methode. The setting up plans for Visual Basic 6.0 programming languange and MySQL database. The result showed that the highest value for the type olympiad subject. And then the equal with all olympiad subject.